Scientific Contributions and Legacy of Prof. Stanisław Kasznica in the Memories of Prof. Józef Filipek and Prof. Janusz Homplewicz (Contemporary Central & East European Law, 2024)
The article presents unknown or little-known aspects of the life of prof. Stanisław Kasznica and his family. In particular, Krakow threads were presented, including the memories of prof. Józef Filipek and prof. Janusz Hoplewicz.